2021
DOI: 10.1038/s41598-021-98684-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide stress sensitivity moderates the stress-depression relationship in a nationally representative sample of adults

Abstract: We re-evaluate the findings of one of the most cited and disputed papers in gene-environment interaction (GxE) literature. In 2003, a paper was published in Science in which the authors demonstrated that the relationship between stress and depression is moderated by a polymorphism in the promoter region (5-HTTLPR) of the gene SLC6A4. Replication has been weak and led many to challenge the overall significance of GxE research. Here, we utilize data from Add Health, a large, nationally representative, and well-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Susceptibility to environmental influences is not a binary variable, but a continuous variable with an assumed normal distribution, ranging from low to high [ 4 ]. According to several prevailing theories [ 5 , 6 ], the interaction between susceptibility genes [ 7 ] and the early environment (both supportive and adversarial) [ 8 ] shapes the susceptibility of the central nervous system. When highly sensitive individuals are exposed to certain environmental stimuli, an increase in neurophysiological reactivity is observed (e.g., activation of the amygdala and insular cortex; [ 9 ]), along with behaviors exhibiting heightened sensitivity (e.g., difficult temperament; [ 10 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Susceptibility to environmental influences is not a binary variable, but a continuous variable with an assumed normal distribution, ranging from low to high [ 4 ]. According to several prevailing theories [ 5 , 6 ], the interaction between susceptibility genes [ 7 ] and the early environment (both supportive and adversarial) [ 8 ] shapes the susceptibility of the central nervous system. When highly sensitive individuals are exposed to certain environmental stimuli, an increase in neurophysiological reactivity is observed (e.g., activation of the amygdala and insular cortex; [ 9 ]), along with behaviors exhibiting heightened sensitivity (e.g., difficult temperament; [ 10 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of the validity of the polygenic plasticity index emerged from research showing it moderated effects of observed parenting quality on children’s emotional development (Keers et al, 2016), explained variation in the efficacy of different types of Cognitive Behavioral Therapy (CBT) for child anxiety disorders (Keers et al, 2016), and explained variation in effects of a family intervention on children’s internalizing symptoms (Lemery-Chalfant et al, 2018). Most recently, the same polygenic score accounted for variability in effects of stressful life events on adults’ depression symptoms (Davidson et al, 2021).…”
Section: The Prevention and Relationship Education Program (Prep)mentioning
confidence: 99%
“…Susceptibility to environmental influences is not a binary variable, but a continuous variable with an assumed normal distribution, ranging from low to high (e.g., Zhang et al, 2021). According to several prevailing theories (e.g., Boyce & Ellis, 2005;Belsky & Pluess, 2009), the interaction between susceptibility genes (Davidson et al, 2021) and the early environment (both supportive and adversarial) (Shakiba et al, 2020) shapes the susceptibility of the central nervous system. When highly sensitive individuals are exposed to certain environmental stimuli, an increase in neurophysiological reactivity is observed (e.g., activation of the amygdala and insular cortex; Acevedo et al, 2014) along with behaviors exhibiting heightened sensitivity (e.g., difficult temperament; Pluess & Belsky, 2011).…”
Section: Individual Differences In Sensory Processing Sensitivitymentioning
confidence: 99%